1979
DOI: 10.1037/0096-1523.5.2.365
|View full text |Cite
|
Sign up to set email alerts
|

Influence of six types of visual structure on complexity judgments in children and adults.

Abstract: Individuals at five grade levels (kindergarten, Grade 2, Grade 4, Grade 6, and college) made pair-comparison judgments of visual complexity. The influence of the presence or absence of six types of visual structure (double symmetry, vertical symmetry, horizontal symmetry, diagonal symmetry, checkerboard organization, and rotational organization) and of amount of contour were examined. Two general developmental trends were revealed: First, the age at which visual structure initially affected complexity judgment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
43
0

Year Published

1985
1985
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 13 publications
3
43
0
Order By: Relevance
“…In particular, symmetry, especially vertical symmetry, is hard to ignore (Chipman, Mendelson, & Morton, 1979;Lachmann & Geyer, 2003;Palmer, 1985). Symmetry perception may be phylogenetically predetermined (Corballis & Beale, 1970;Herbert & Humphrey, 1996;Lachmann & Geyer, 2003).…”
mentioning
confidence: 95%
“…In particular, symmetry, especially vertical symmetry, is hard to ignore (Chipman, Mendelson, & Morton, 1979;Lachmann & Geyer, 2003;Palmer, 1985). Symmetry perception may be phylogenetically predetermined (Corballis & Beale, 1970;Herbert & Humphrey, 1996;Lachmann & Geyer, 2003).…”
mentioning
confidence: 95%
“…Four-year-olds chose randomly, whereas 6-and 8-year-olds were progressively more likely to select the figure with the common higher-order relations. Additional evidence is provided by Chipman and Mendelson (1979), who presented 5-, 7-, 9-, and 11-year-old children with pairs of patterned 248 D. Gentner and M. J. Rattermann displays and asked them to judge relative complexity. They found an age-related increase in the effect of structure on these complexity judgments.…”
Section: Comparing the Effects Of Object Similarity And Relational Simentioning
confidence: 99%
“…However, if an integral part of the interpretation of line graphs is an evaluation of the overall form of the line, then the number of points along the line may have little impact on study times. Instead, global features of the line, such as the presence of symmetry, previously found to mediate assessments of shape complexity (Chipman and Mendelson, 1979), should better predict study times. Additionally, research on directed interpretations of graphs has shown that departures from linearity can be used as efficient response cues (Buttigieg and Sanderson, 1991).…”
mentioning
confidence: 99%